Penerapan Mindfulness-Based Cognitive Therapy Menurunkan Tingkat Stress Pasien Hipertensi: Internalisasi Ontologi Epistemologi, Aksiologi - Misrawati Misrawati; Salsa Adelia Rahmadani; Fera Rahmawati; Endang Dwi Rukmini; Riza Fouzia Khainingsih; Triswan Simatupang (STIKes YARSI Pontianak, 2026)
Background: A significant worldwide health concern that raises morbidity and death, particularly in older persons, is hypertension. Psychological stress can worsen blood pressure, making non-pharmacological approaches such as Mindfulness-Based Cognitive Therapy (MBCT) valuable. This study applies MBCT using the Neuman Systems Model while integrating ontological, epistemological, and axiological principles of nursing. Objective: To assess how well MBCT reduces stress in people with hypertension and to identify the integration of nursing philosophical values in the intervention. Methods: The intervention was carried out over three days at Puskesmas Simpang Tiga, Pekanbaru. Activities included education on stressors, guided mindfulness meditation, and reflective stress-management sessions. Stress and mindfulness levels were assessed before and after the intervention using the Perceived Stress Scale (PSS-10) and the Mindful Attention Awareness Scale (MAAS). Results: Most participants showed reduced blood pressure and decreased stress scores after the intervention. Mindfulness levels also increased. Ontological values were reflected in viewing patients as holistic beings; epistemological values through evidence-based practice; and axiological values through empathy and ethical nursing care. Conclusion: When used as a non-pharmacological treatment, MBCT helps individuals with hypertension feel less stressed. The intervention strengthens holistic nursing practice grounded in ontological, epistemological, and axiological principles.